THE IMPACT OF COLORS ON OUR BEHAVIOR AND HEALTH - Ibragimov Rustam Qudratovich; Sattorova Aziza Anvarovna (International Engineering Journal For Research & Development, 2020)
When a person lives, he seeks beauty, every beauty, the environment consists of colors. Colorless perception of life can not be achieved. It is difficult to imagine the beauty of life in general without color. The correct or incorrect use of colors can have a positive or negative impact on a person's health.